Enterotoxigenic Escherichia Coli subclinical infection in pigs: bacteriological and genotypic characterization and antimicrobial resistance profiles - Moredo, Fabiana A. (2015)
Enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for neonatal diarrhea, postweaning diarrhea, and edema disease in pigs. Although it can be harmless, ETEC is also present in the intestines of other animal species and humans, causing occasional diarrhea outbreaks. The evaluation of this pathogen’s presence in food sources is becoming an increasingly important issue in human health. In order to determine the prevalence of ETEC in nondiarrheic pigs, 990 animals from 11 pig farms were sampled. Using end-time polymerase chain reaction (PCR), eltA, estI genes, or both, were detected in 150 (15.2%) animals. From the positive samples, 40 (26.6%) ETEC strains were isolated, showing 19 antibiotic-resistance patterns; 52.5% of these strains had multiple antibiotic resistances, and 17.5% carried the intI2 gene. The most prevalent genotypes were rfbO157/estII/aidA (32.5%) and estI/estII (25.0%). The estII gene was identified most frequently (97.5%), followed by estI (37.5%), astA (20.0%), and eltA (12.5%). The genes coding the fimbriae F5, F6, and F18 were detected in three single isolates. The aidA gene was detected in 20 ETEC strains associated with the estII gene. Among the isolated ETEC strains, stx2e/estI, stx2e/estI/estII, and stx2e/estI/estII/intI2 genotypes were identified. The ETEC belonged to 12 different serogroups; 37.5% of them belonged to serotype O157:H19. Isolates were grouped by enterobacterial repetitive intergenic consensus–PCR into 5 clusters with 100.0% similarity. In this study, we demonstrated that numerous ETEC genotypes cohabit and circulate in swine populations without clinical manifestation of neonatal diarrhea, postweaning diarrhea, or edema disease in different production stages. The information generated is important not only for diagnostic and epidemiological purposes, but also for understanding the dynamics and ecology of ETEC in pigs in different production stages that can be potentially transmitted to humans from food animals.